Multiphysics Coupling Simulation and Parameter Study of Planar Solid Oxide Fuel Cell - Dang, Zheng; Shen, Xin; Ma, Jinyan; Jiang, Zhaoyi; Xi, Guang (Frontiers in Chemistry, 2021)
In this paper, a numerical model of multi-physics coupling of a planar SOFC is established and solved. According to the calculation results, the distribution of various physical parameters inside the SOFC cell is analyzed. The influence of cathode inlet flow rate, porosity, rib width and other parameters on the performance of SOFC is also discussed. The results show that within a certain range, increasing the cathode inlet flow rate can significantly increase the average current density of the cell. Increasing the porosity of the electrode can improve the gas diffusion of the porous electrode, thereby increasing the rate of the electrochemical reaction. Increasing the width of the ribs will result in a significant decrease in cell performance. Therefore, the rib width should be reduced as much as possible within the allowable range to optimize the working performance of the cell.